Green Marketing and Its Impacts on Consumer Behavior in Sports Shops - Javad Shahlaee (The Society of Aging and Physical Activity (SAPA), 2014)
The aim of this study was investigation of green marketing and its impacts on consumer behavior in sports shops in East Azerbaijan province of Iran. The present study is functionalized by objectives and done by field. The study statistical society was sports shops in East Azerbaijan and 210 samples were chosen randomly according to Morgan sampling method and 196 questionnaires were collected finally. The author-prepared questionnaire's validity was approved by some experts in sport management and marketing. Field and the reliability were assessed by pilot study using Chronbach's Alpha (α= 819%) which showed that the tool was reliable. The questionnaire had 30 items rated by Lakers scale. Questionnaire introduction contained demographic pieces information of age, income and education degree. Results shows that a significant relationship between green products features, green promotion, green pricing and green distributing with consumer green behavior; and education, income, and age, but not marital status, gender had a moderating effect on consumer green sports behavior.